An Emerging Liquid-Crystalline Conducting Polymer Thermoelectrics: Opportunities and Challenges - Ye, Zhenqiang; Zhang, Mingdong; Deng, Junyang; Liang, Lirong; Du, Chunyu; Chen, Guangming (Nano-Micro Letters, 2025)
Thermoelectric (TE) materials, being capable of converting waste heat into electricity, are pivotal for sustainable energy solutions. Among emerging TE materials, organic TE materials, particularly conjugated polymers, are gaining prominence due to their unique combination of mechanical flexibility, environmental compatibility, and solution-processable fabrication. A notable candidate in this field is poly(2,5-bis(3-alkylthiophen-2-yl)thieno[3,2-b]thiophene) (PBTTT), a liquid-crystalline conjugated polymer, with high charge carrier mobility and adaptability to melt-processing techniques. Recent advancements have propelled PBTTT’s figure of merit from below 0.1 to a remarkable 1.28 at 368 K, showcasing its potential for practical applications. This review systematically examines strategies to enhance PBTTT’s TE performance through doping (solution, vapor, and anion exchange doping), composite engineering, and aggregation state controlling. Recent key breakthroughs include ion exchange doping for stable charge modulation, multi-heterojunction architectures reducing thermal conductivity, and proton-coupled electron transfer doping for precise Fermi-level tuning. Despite great progress, challenges still persist in enhancing TE conversion efficiency, balancing or decoupling electrical conductivity, Seebeck coefficient and thermal conductivity, and leveraging melt-processing scalability of PBTTT. By bridging fundamental insights with applied research, this work provides a roadmap for advancing PBTTT-based TE materials toward efficient energy harvesting and wearable electronics. Highlights: 1 Poly(2,5-bis(3-alkylthiophen-2-yl)thieno[3,2-b]thiophene) (PBTTT) synthesis and main strategies to enhance its thermoelectric performance (including doping, composite engineering and aggregation state controlling) are comprehensively reviewed. 2 The thermoelectric performances of PBTTT-related materials are systematically summarized and compared. 3 Future opportunities of PBTTT thermoelectric performance enhancement and effective utilization of its unique melt processibility in multiscale regulation, composite and hybrid, and processing technology innovation are outlooked.